The geophagic nature of financial dominance in the Brazilian real estate market - Simoni Santos, César (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Since the 1980s, following the re-concentration of economic activity in metropolitan regions, the urban real estate market in Brazil has been emerging as a sector that is capable of profitably absorbing the surplus produced in an economy that is facing a crisis. Initially, it is organized around the demand that is concentrated, in terms of space and sector, in the new business centralities. After the sector established a more dependent bond with the capital market, a relationship represented by a wave of Initial Public Offerings (IPOs) by major real estate companies, the effects of the North American mortgage crisis were not trivial. An important movement of capital flight took place in the Brazilian stock market from thenceforth. The largest public housing program in the history of the country, the Minha Casa Minha Vida (MCMV, ‘My Home My Life’) program, was launched during that period, less than a year after the 2008 crisis. The targeted production of real estate that followed had new characteristics in terms of geographic behavior and its relationship with land. This paper aims to shed light on some critical events that led to this scenario and discuss some aspects of this change that are essential for the real estate business to maintain its position as one of the most profitable and promising investments in Brazil. The geographical behavior of real estate investment, considering its tendency to expand and intensify, plays a decisive role in this context.